Sorcery or Science? : Contesting Knowledge and Practice in West African Sufi Texts - Marcus-Sells, Ariela, 1985- (Book collections on Project MUSE., 2022)
"Examines the works of two Sufi Muslim scholars, Sīdi al-Mukhtār al-Kuntī (d. 1811) and his son Sīdi Muḥammad (d. 1826), focusing on their cosmology and metaphysics of the realm of the unseen, in relation to the history of magical discourses within the Hellenistic and Arabo-Islamic worlds"--